O difícil caminho da reforma: A polícia e os limites do processo de reforma pós-redemocratização - Souza, Luís Antônio Francisco de [UNESP]; Battibugli, Thais (My University, 2014)
A transition of Brazil from a juridico-political system of exception to a democracy was accompanied by several legal and institutional reform processes, aimed at the gradual elimination of so-called authoritarian rubble and the implementation of instruments of the democratic system, based on recognized citizenship and justice. However, to this day the extent and effects of those reforms can be questioned, especially in light of the increased public demand for justice and citizenship. The article The Difficult Path to Reform: The Police and Limits of the Post-Redemocratization Reform Process shows that the route to reform, above all in the sphere of police agencies, is a tortuous one, with an extensive agenda of problems and solutions, demanding research on the part of academics in order to form an understanding of the resistance to change and to new paradigms that define the public security agenda.

A passagem do Brasil de um sistema político-jurídico de exceção para a democracia foi acompanhada de inúmeras reformas legais e institucionais, que tiveram como escopo a eliminação gradual do chamado entulho autoritário e a implantação dos instrumentos do sistema democrático, baseado no reconhecimento da cidadania e da justiça. No entanto, ainda hoje se avaliam a extensão e os efeitos das reformas, sobretudo diante da ampliação da busca popular por justiça e cidadania. O caminho da reforma, principalmente no âmbito das agências policiais, é tortuoso e a agenda dos problemas e soluções é grande, o que demanda da academia pesquisas para compreender a resistência à mudança e novos paradigmas definidores da agenda da segurança pública.
Keywords: Polícia; Reforma da Polícia; Segurança Pública; Políticas Públicas; Violência Policial